LA REGULACIÓN DE LA POSESIÓN Y SUCESIÓN, DE LAS AUTORIDADES DE ELECCIÓN POPULAR EN CASOS DE FALLECIMIENTO - Guamán González., Manuel Leonardo (2019)
This thesis constitutes the final report of the investigation process carried out and motivated in the Ecuadorian legislation, the same one that carries by title: "Regulation of the possession and succession of the authorities of popular election in cases of death" Its importance lies in the knowledge of a legal problem in the Electoral Organic law and political organizations of the Republic of Ecuador, Code of democracy. Since it does not establish the form of succession in the case of the death of the winners to a dignity of popular choice, who would want to happen? There is no response within the Ecuadorian legal system, generating a conflict since the political interests are diverse and in the absence of the norm to settle a solution, generates legal uncertainty. In this circumstance it is feasible to deepen my study with the purpose of proposing alternatives of legal reform. That is why I consider it necessary to reform the organic Electoral law and of political organizations of the Republic of Ecuador, the Code of democracy to guarantee the right to participate in democracy, transparency and the order of succession for the possession of Popular election authorities.